Effectiveness of Early Childhood Education: A Case Study from Remote District of Central Punjab - Safdar Rehman Ghazi, Muhammad Ajmal, Asif Saeed (JECCE, 2023)
This study was designed to the effectiveness of early childhood education classrooms in terms of available facilities and practices in Public Elementary Schools of remote district of central Punjab. In this study survey design was used. The target population for this study was all the Head Teachers, ECE teachers and Caregivers constituted the population working in all public elementary schools in district Toba Tek Singh. However, using simple random sampling method 150 head teachers, 150 teachers and 150 caregivers (female) were selected. To collect data from the sampled participants a self-developed questionnaire was used as data collection instrument from the sample. The items set in the questionnaire was based on categories of Facilities and Practices. The questionnaire was also pretested on a small group of teachers from non-selected schools to evaluate the validity and reliability of the questionnaire. The Cronbach alpha value for reliability of the questionnaire was found 0.71. It was found that there was scarcity of multimedia or projector, first aid box, washrooms, energy sources, necessary stationery, drinking water and new charts to restore the interest in learning of the kids in ECE rooms. Lack in teachers and caregivers use of different pedagogies to inculcate the basic concepts and making the